The Role of the Sabhara Unit Patrol in Preventing Crime Theft of Two-Wheeled Motorized Vehicles Maintenance of Public Security and Order (Harkamtibmas) at the Kuningan Police - Wiratama, Adhitya (Advances in Police Science Research Journal, 2020)
This research is motivated by the condition of development of criminal acts of vehicle theft that occured in Indonesia, whose existence is still make public worry. Law enforcement and rehabilitation actions have not resolved the problem, so the most effective action is prevention. The preventive action is the form of a patroli carried out by the Sabhara Unit which in this case the target focus is the people of Kunigan Regency. the theft of vehicles, especially two-whelled vehicles, is widespread and disrupts the Kuningan Regency public order and safety. Research is conducted to find out the efforts to optimize the Sabhara Unit patrols against the people of Kuningan Regency. The study was conducted with a ualitative approach, analytical descriptive research methods, and data collection techniques through observation, interview, and document review. The result of the study analyzed with Crime Prevention Theory, Management Theory, Routine Activity Theory, Communication Theory, and Patrol Concept show that management in the implementation of Sabhara unit patrols in preventing criminal acts of two-wheeled vehicle is still not optional. THere are discrepancies in some of the activities contained in the patrol concept in accordance with the Head of Security Maintenance Regulation No. 1 of 2017 concerning Patrol. Then the ability and readiness of the officers in carrying out patrol activities was still lacking. Especially in ability of communication with peolple. Based on the results of the study, the author suggest that increased activities in the implementation of patrol and the delivery of public order and safety messages extend to all areas of Kuningan Police jurisdiction so that acts of two-wheeled vehicle theft in large areas can be prevented. Then for the supervision of each patrol implementation in accordance with the standard operating procedures that already exist in the Head of Security Maintenance Regulations without adding or substracting the points. Then provide vocational education and development to personnel so that they have competence in patrol duties and can carry out patrol responsibilities well. And by forming a standard operating procedures planning and drafting team so that the personnel in charge of patrol know clearly their duties and responsibilities, fulfill their tasks and the objective of maintaining public order and safety are realized.